(untitled) (El Hilo de la Fabula, 2025)
In 1951 the poem Masaccio, written by Julio Cortázar, was published in the number 195/196 of Sur magazine. What was the relationship between the Argentinian writer and the Italian literature in those first years of activity? What were the value and impact of the direct observation of some artistic paintings in Florence? This article focuses on the genesis of the poem Masaccio and presents some similarities between Cortazar’s poem and Eugenio Montale’s poetry included in Ossi di Seppia (1925).